2013
DOI: 10.4067/s0718-58392013000300002
|View full text |Cite
|
Sign up to set email alerts
|

Paddy plants inoculated with PGPR show better growth physiology and nutrient content under saline conditions

Abstract: The possible role of plant growth-promoting rhizobacteria (PGPR) to alleviate salt stress during plant growth has been studied on paddy rice (Oryza sativa L.) 'GJ-17' under greenhouse conditions; the study included growth parameters, mineral concentration, and antioxidant enzyme level. Salinity reduced plant growth, but PGPR inoculation reduced its harmful effect up to 1% salinity. Plants inoculated with PGPR under saline conditions showed 16% higher germination, 8% higher survival, 27% higher dry weight, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 22 publications
(21 reference statements)
2
33
0
Order By: Relevance
“…and Bacillus cereus . Furthermore, Jha and Subramanian ( 2013 ) showed clearly the direct and potential effect of some osmotolerant bacteria on germination of paddy seeds under saline conditions. This is probably due to the intervention and supplementation of IAA by the inoculated bacteria which plays an important role in the germination of seeds.…”
Section: Phytohormone Production Of Pgpbmentioning
confidence: 99%
See 2 more Smart Citations
“…and Bacillus cereus . Furthermore, Jha and Subramanian ( 2013 ) showed clearly the direct and potential effect of some osmotolerant bacteria on germination of paddy seeds under saline conditions. This is probably due to the intervention and supplementation of IAA by the inoculated bacteria which plays an important role in the germination of seeds.…”
Section: Phytohormone Production Of Pgpbmentioning
confidence: 99%
“…In addition to these characters, these rhizobacteria showed the potential to fi x nitrogen and solubilize phosphate under high salinity conditions (Sarathambal and Ilamurugu 2013 ). Osmotolerant rhizobacteria are known to enhance nutrient uptake in plants, nitrogen fi xation, phosphate solubilization and siderophore biosynthesis in saline soils (Bashan et al 2000 ;Ibekwe et al 2010 ;Chakraborty et al 2011 ;Shookietwattana and Maneewan 2012 ;Aamir et al 2013 ;Jha and Subramanian 2013 ;Younesi et al 2013b ). In addition, the inoculation with osmotolerant PGPB to alleviate the deleterious effects of salt stress conditions on growth and yield of strawberry plants under salinity conditions was examined by Karlidag et al ( 2013 ).…”
Section: Minerals Uptake Nitrogen Fixation Siderophores Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathivanan et al, (2014) reported that the combination of plant growth promoting rhizobacteria enhanced the root weight. Jha and subramanian, (2013) also reported that the plants inoculated with PGPR showed higher dry weight. So far as interaction effect for the root weight, shoot weight, and total biomass were concerned, the combination of treatment, S 4 T 8 (26.01 mg), (575.12 mg), and (601.13 mg) respectively recorded significantly highest value.…”
Section: Root Fresh Weight Shoot Fresh Weight and Total Biomass (Mg)mentioning
confidence: 94%
“…Besides, potassium is essential for the photosynthesis process and acts as a key for photosynthesis enzymes to initiate the formation of carbohydrate, which is metabolized into amino acids and proteins in the plant. Plants inoculated with Pseudomonas and Bacillus (KSM) in non-saline conditions, as well as at different level of salinity, showed significantly high leaf greenness and photosynthetic rates compared with non-inoculated control plants (Jha and Subramanian 2013c). The plants inoculated with KSM showed 3-5 % higher leaf greenness in the control condition and 2-10 % under salinity.…”
Section: Effect Of Ksm On Photosynthesis Under Saline Stress In Plantsmentioning
confidence: 98%